POSSIBILITY OF A LOW-COST ARDUINO-BASED CRASH DETECTION AND ALERT SYSTEM - Wisesa, Rakean Shidqii Hasan Ali; Parsa , Nuriya; Pakpahan, Pahala Marzuki; Azahra, Loviera; Nurhidayatulloh (Komunitas Menulis dan Meneliti (Kolibi), 2024)
This paper introduced a possible concept for a crash detection system, designed to enhance road safety for both cars and motorcycles. The system is built on the Arduino platform, it aims to be a cost-effective crash detection system, that can detect crashes immediately and warn the emergency contacts, as soon as the crash happens, using its emergency protocol, upon detecting a crash, the Arduino will fetch the location data from the GPS module, which it will send to the emergency contacts using text message, utilizing it's GSM module. Enabling faster response time and increased survival rate for the crash victims. Our tests which focus on the accuracy of the accelerometer module have found that it has promising results, but still needs more research into increasing its accuracy to avoid false positives and undetected crashes